Optimalisasi Pengelolaan Sarana dan Prasarana di Mahad Aisyah Bogor Melalui Implementasi Siklus Aset - Sonia, Gina; Darma, Surya Hadi (Addabani: Interdisciplinary Journal of Islamic Education, 2025)
Asset management, especially facilities and infrastructure, is essential in ensuring educational institutions' operational effectiveness. This study analyzes the application of the asset cycle in managing facilities and infrastructure at Mahad Aisyah Bogor. The asset cycle includes planning, management, inventory, legal audit, valuation, operation, maintenance, renewal, and elimination. The research method used is qualitative, with an observation, interview, and documentation study approach. The results showed that asset management in Mahad Aisyah is carried out systematically. However, there are obstacles to implementing each stage, such as evaluation and development, which must be done regularly. The analysis found that good asset management can improve service quality and support achieving the institution's vision and mission. In addition, proper maintenance and periodic renewal of assets are key to maintaining the effective functioning of facilities and infrastructure. Recommendations from this study emphasize the need to strengthen the human resources capacity to implement the asset cycle and provide adequate resource support to achieve optimal success.